Avaliação da percepção de fala e benefícios do uso de aparelhos de amplificação sonora individual em idosos - Viviane Racioppi da Rocha Morgan (2022)
Introduction: Studies show improvement in auditory skills after hearing aid fitting. Its use also brings several benefits, including improved quality of life. It is therefore important to measure the effect of the use of hearing aids on the speech recognition index and on the user's self-perception of its benefits. Objective: Verify the effect of hearing aid fitting on speech recognition and on the self-perception of its benefit in the elderly. Methods: Experimental, longitudinal study with 35 elderly users of bilateral hearing aids, carried out in two stages: at the time of fitting the devices and six months later. Procedures performed: pure tone audiometry, IPRF, application of HHIE-s and IOI-HA questionnaires and recording of the average time of daily use of the hearing aid. Analyzes were performed: descriptive of the characterization of the sample, IPRF, HHIE-s, IOI-HA and average time of use of the device; comparison between the results of the IPRF and the HHIE-s in the two stages using the Wilcoxon test; correlation between the results of the questionnaires, IPRF and time of use of the hearing aid by the Spearman test; and association between time of hearing aid use (categorized as > or < 8h) with IPRF, HHIE-s and IOI-HA by the Mann-Whitney test. The significance level adopted was 5%. Results: Sample composed of 35 participants (14 men and 21 women), with a minimum age of 60 years, a maximum of 89 years and the average of 75.37 years. All participants had bilateral sensorineural hearing loss, ranging from mild to moderately-severe. Comparing the two moments, the average percentage of the IPRF had an improvement in the monosyllable and disyllable lists and there was a moderate correlation of this improvement with the average time of daily use of the hearing aid; the HHIE-s questionnaire score showed a significant reduction; IOI-HA presented a mean score of 29 points; the average time of daily use of hearing aids was, for the most part (57.1%), less than eight hours a day. Conclusion: In the population studied, the use of hearing aids contributed to the improvement in speech recognition, reduction in the perception of the effects of hearing loss and self-perception of the benefit of using the devices.